The Developing World’s Depiction in the Battlefield and Call of Duty Video Game Series. Does It Replicate the Stereotypical Image? - Ząbecki, Krzysztof (Regional Barometer. Analyses & Prognoses, 2015)
The purpose of this paper is to analyze how the Third World is presented in the highly popular Battlefield and Call of Duty video game series and whether the games replicate the Global South’s stereotypical image. In the introduction, the term “stereotype” is defined, countries or regions to be considered “developing” are distinguished, and the choice of video games to be examined in the study is made. Then, the content of the chosen games is analyzed in order to find elements of the environment that are represented, the sides of the depicted conflicts, their place and background, as well as playable characters and enemies. In the conclusion, the developing world’s depiction is compared to the already existing stereotypes in order to decide to what extent and in what aspects video games repeat them.